Coronavirus XBB.1.5 as an Indicator of the Long-Term Continuation of the Covid-19 pandemic. What Next for Vaccination? - E. P. Kharchenko (Эпидемиология и вакцинопрофилактика)
The article discusses the properties of the pandemic strain XBB.1.5 S protein in comparison with the 1918 and 2009 pandemic strains hemagglutinin H1. The S-protein XBB.1.5 already contains more than 40 mutations realized by substituting different amino acids through single and dinucleotide substitutions, deletions and the use of predominantly transversions. The variability of H1N1 influenza virus hemagglutinin is associated with single nucleotide substitutions at a constant length. Conditional extrapolation of influenza virus hemagglutinin variability data on coronavirus S-protein sizes suggests that new pandemic strains will emerge in the next 2-3 years, avoiding the immune defense formed by vaccination against the strains preceding them. The inability to create through the adaptive immune system a long-term immunity to pandemic coronaviruses, as well as to other respiratory viruses with a short incubation cycle, puts on the agenda the need to find new vaccine designs that provide a combination of long-term adaptive and trained immunity. The problem in the search for such vaccines is associated with the regulation of the activity of the innate immune system and ensuring the stability of trained immunity.